The Influence of Innovation, Creativity, and Risk-Taking on Entrepreneurial Growth and SMEs Performance in Sukabumi City - Yana Priyana; Rahmawati Syam; Dahlan Dahlan (West Science Business and Management, 2023)
This study explores the influence of innovation, creativity, and risk-taking on entrepreneurial growth and SMEs performance in Sukabumi City, Indonesia. A survey was conducted with 150 SMEs in the region to collect data on their innovation, creativity, risk-taking behavior, and performance indicators. The results suggest that innovation and creativity significantly impact SME growth and performance, while risk-taking has a weaker impact. These findings have important implications for policymakers and SMEs owners or managers in Sukabumi City and other regions with similar economic contexts, highlighting the need to promote and support innovative and creative practices among SMEs.